The impact of deficit financing on economic stability : the case of Jordan - Kasasbeh, Hamad A. (Array, 2019)
This study examines the effect of deficit financing on economic stability in Jordan during the period 2005-2017, using quarterly data by employing the Vector Error Correction Model (VECM) after seasonally adjusting the variables. This paper is unique as it is the first of its kind that tackles the issue of stability in Jordan. It provides empirical evidence that external borrowing (EBDT) and domestic bank financing (BANK) negatively affect economic stability in Jordan. The bank effect is due to crowding out the private sector. External borrowing negative impact is driven by the current high level of outstanding public debt, 98 percent of GDP. Public debt is mainly channeled to finance current expenditures at the expense of capital expenditures, which has a minimal impact on growth. Interest rate (REPO) effect is in line with the finance theory as higher rates lead to lower growth. Non-bank financing (NonBank), although not statistically significant, exhibits the right sign as it has a positive effect. Future research may extend this work by including other macroeconomic variables such as current account deficit, money supply and direct foreign investment.